2019
DOI: 10.1007/s12640-019-00040-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Elastin-Derived Peptide VGVAPG on SH-SY5Y Neuroblastoma Cells

Abstract: Throughout the lifetime of humans, the amount of stem cells and the rate of cell proliferation continue to decrease. Reactive oxygen species (ROS) are one among the many factors that promote stem cell aging. Both a decrease in the level of stem cells and increase in ROS production can lead to the development of different neurodegenerative diseases. This study was conducted to determine how the VGVAPG peptide, liberated from elastin during the aging process and under pathological conditions, affects ROS product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…Our previous studies have shown that the VGVAPG peptide increases ROS production in an EBP-dependent manner in mouse primary astrocytes in vitro 32 . Similarly, an increase in ROS production after EDP stimulation has been reported in monocytes, human fibroblasts, and a neuroblastoma (SH-SY5Y) cell line 29,30,33 . Moreover, EDPs have been described to enhance the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), or glutathione peroxidase (GPx), and increase lipid peroxidation in human fibroblasts 40 .…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Our previous studies have shown that the VGVAPG peptide increases ROS production in an EBP-dependent manner in mouse primary astrocytes in vitro 32 . Similarly, an increase in ROS production after EDP stimulation has been reported in monocytes, human fibroblasts, and a neuroblastoma (SH-SY5Y) cell line 29,30,33 . Moreover, EDPs have been described to enhance the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), or glutathione peroxidase (GPx), and increase lipid peroxidation in human fibroblasts 40 .…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, EDPs have been described to enhance the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), or glutathione peroxidase (GPx), and increase lipid peroxidation in human fibroblasts 40 . Furthermore, the VGVAPG peptide increases the expression and activity of GPx in SH-SY5Y cells 33 . On the other hand, the VGVAPG peptide reduced ROS production in neutrophils in controls and patients with stable chronic obstructive pulmonary disease 28 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because resistin is strictly controlled by PPARγ activation, our data allow to assume that VGVAPG peptide by interaction with this receptor can control resistin gene expression [88]. Interaction between PPARγ and VGVAPG has been proven in our previous study, in which VGVAPG peptide was shown to affect PPARγ expression and PPARγ-mediated effects in mouse astrocytes and SH-SY5Y cells [31,49]. As mentioned above, PPARγ is involved in resistin expression, which is strictly related to obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 52%
“…It is well known that EDPs or VGVAPG increase ROS production in different cells such as murine monocytes and astrocytes, human fibroblasts, and neuroblastoma (SH-SY5Y) cells [49][50][51][52][53]. Moreover, ROS are key signalling molecules that play an important role in the progression of inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%